How does Digital Transformation reshape the Multinationals\' operations in an emerging country? An evolutionary process research. - Fisch, Flávio (2021)
This thesis investigates how and why Digital Transformation (DT) is reshaping multinational firms\' operations. The two models addressing the international manufacturing networks, here dubbed inner international networks (IINs), were published in the 1990s but still ground the literature on international operations management. In 1997, Kasra Ferdows proposed the first model, about the roles of foreign factories. In 1998, Shi and Gregory published the second model, depicting the configuration and coordination of IINs, Using a systematic literature review about international operations management and DT and intersecting the two literature results, we extract the few articles addressing the transformations that digital technologies promote in the MNE\'s operations. We synthesize three DT strategies - Integration, Servitization, and Relocation - and four DT journeys - IIN Integration, LifeCycle Integration, Digitally Enabled Servitization, and Relocation - that contrast the traditional models\' assumptions and build our conceptual framework. This exploratory study uses the evolutionary process case research method to investigate seven embedded cases in five multinationals operating in Brazil. In this research, we retrospectively cover the DT\'s period of implementation. We propose a new framework that extends the traditional plant- and network-level models based on the technological and organizational changes that DT promotes to the firms\' international operations. Our proposal includes theoretical contributions like the introduction of DT into the field of international operations management, the mechanisms DT promotes to change the IIN and its sites like the displacement of activities from the site level to the network level, the inclusion of sites that contribute to the network with functions other than production, and the ecosystem construct\'s introduction to support describing the complex network participants\' relations. We also offer an updated typology to describe new network coordination and plant roles, the Digitally Enabled Multinational Inner Network - DEMIN. The thesis brings new perspectives for understanding how multinationals reorganize their operations, now and in the future, in times of deglobalization accelerated by pandemics. There is also a reflection about the role of multinationals\' operations in emerging countries like Brazil. Finally, the thesis lists practical implications to managers, firms, and governments.